2015
DOI: 10.1002/hrm.21715
|View full text |Cite
|
Sign up to set email alerts
|

Guest Editors' Introduction: Diversity and Inclusion in Different Work Settings: Emerging Patterns, Challenges, and Research Agenda

Abstract: The purpose of this paper is to analyze and highlight the developments in the current scholarship on managing diversity and inclusion (D&I) and provide insights for future research. While doing so the paper advances our understanding of 'what matters' in this field, through the integration of different literature concerning the dimensions of D&I. It also provides a neoinstitutionalist framework, which locates different themes in the D&I, scholarship to assist in further development of the field. It argues for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 162 publications
0
79
0
2
Order By: Relevance
“…Diversity experts have suggested that organizational support for diversity can have performance‐enhancing benefits for organizations, and research generally supports this proposition (Richard, ; Theodorakopoulos & Budhwar, ). This logic is often used by organizations when explaining the potential benefits of CSR programs and socially responsible behavior, such as the adoption of diversity‐enhancing policies.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversity experts have suggested that organizational support for diversity can have performance‐enhancing benefits for organizations, and research generally supports this proposition (Richard, ; Theodorakopoulos & Budhwar, ). This logic is often used by organizations when explaining the potential benefits of CSR programs and socially responsible behavior, such as the adoption of diversity‐enhancing policies.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…From a stakeholder perspective, as more firms implement LGBT‐supportive policies, a company's decision not to adopt such rules may send a signal to potential employees that the firm is not socially responsible when it comes to antidiscrimination and support for diversity. Indeed, support for a variety of forms of diversity and inclusion seems increasingly “in vogue” (Theodorakopoulos & Budhwar, ). Recent research suggests that LGBT‐supportive policies and practices are increasingly important to workers regardless of their sexual orientation.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Within the literature it is evident that the role of managers within work–life balance is important and those advocating a business case for managing diversity more generally note the importance of their support (Theodorakapoulos and Budhwar, ). As Den Dulk et al .…”
Section: Work–life Balance and Managerial Discretionmentioning
confidence: 99%
“…This is because increased diversity can lead to a better understanding of local markets and customers, a greater ability to attract and retain talent, increased creativity, problem solving, and flexibility for organizations (e.g., Cox & Blake, ; Subeliani & Tsogas, ). Although numerous scholars in HRM have examined work‐related factors that lead various demographic groups to be satisfied at work (Ariss, Vassilopoulou, Özbilgin, & Game, ; Cooke & Xiao, ; Kooij, Jansen, Dikkers, & De Lange, ), far fewer have focused on those who are disabled or are impaired in a way that limits their activity yet allows for gainful employment (Stone & Colella, ; Theodorakopoulos & Budhwar, ). Understanding factors that are associated with the satisfaction of disabled employees is important given that disabled individuals constitute an underutilized labor pool, they have the potential to bring about the aforementioned benefits of diversity, and in most cases, are just as able and motivated to be successful at work relative to their nondisabled counterparts (Ali, Schur, & Blanck, ; Lengnick‐Hall, Gaunt, & Kulkarni, ; Schur et al, ).…”
Section: Introductionmentioning
confidence: 99%